Whole-Rock Pb Isotope Delineation of Archean and Paleoproterozoic Crustal Terranes in the Grenville Province and Adjacent Makkovik Province: Evidence for Juvenile Crustal Growth during the Paleoproterozoic - Arcuri, Gabriel (My University, 2016)
The Grenville Province and adjacent Makkovik Province represent two long-lived ancient orogenic belts that contain remnants of Paleoproterozoic crust accreted to the southeastern Laurentian margin during the Great Proterozoic Accretionary Orogen (GPAO). However, the addition of juvenile Paleoproterozoic crust to the Archean craton during this period was followed by a span of intermittent ensialic arc magmatism and high-grade metamorphism that overprinted much of the early- to mid- Proterozoic geologic history of the region. As a result, these ancient orogenic belts contain cryptic terrane boundaries that require extensive geochronologic mapping in order to reconstruct the accretionary and collisional growth of the southeastern Canadian Shield. Accreted Proterozoic terranes in the Grenville and Makkovik Provinces have been previously mapped using Nd isotopes in order to determine their crustal formation ages and the boundaries between them. Since the U-Pb isotope system has completely different chemical behaviour to the Sm-Nd system, whole-rock Pb isotope analysis provides an independent method to test the results of Nd isotope analysis. Likewise, Pb isotope mapping acts as a useful tool for determining the exhumation of highly metamorphosed crust, as uranium is preferentially transported from lower crustal levels into the upper crust during regional metamorphism. Therefore, whole-rock Pb isotope analysis was performed on over 200 Archean and Proterozoic gneisses from the SW Grenville Province and Makkovik Province in order to 1) differentiate areas of accreted Paleoproterozoic crust from the reworked Archean margin, 2) test the location of the Archean-Proterozoic suture previously mapped in both regions by Nd model ages, and 3) investigate the variable degrees of crustal burial-uplift within the Archean foreland of the SW Grenville Province that was exhumed during the Grenville orogeny. In the Makkovik Province, whole-rock Pb isotope data from the Cape Harrison domain are comparable with published Pb data from the central Ketilidian mobile belt of southern Greenland. The similarity in Pb signatures between the two belts points to a crustal component in the Cape Harrison domain that was derived from a Proterozoic mantle-derived source with minimal input from older Archean crust. This is largely different from published Pb signatures for the Aillik domain in southeastern Labrador and border zone in southern Greenland that suggests a crustal component comprised of reworked Archean crust analogous to the pre-Makkovikian Laurentian foreland. Comparison of new and published Pb data from the Makkovik Province and southern Greenland in turn helps to constrain a revised single arc accretionary model for the Makkovik Province. Previous Nd isotope mapping in the SW Grenville Province revels a break in model ages inferred by authors as a cryptic collisional suture between the reworked Archean foreland and an accreted Paleoproterozoic arc. However, some workers have suggested that this terrane actually consists of Archean crust that was magmatically reworked in the Mesoproterozoic. Whole-rock Pb isotope data presented in this study points to a crustal component south of the proposed suture in Ontario that was derived from a Paleoproterozoic mantle source and subsequently reworked by ensialic arc magmatism during the Mesoproterozoic. North of the suture, Pb data reveals an Archean crustal component analogous to reworked Superior basement that was exhumed from different crustal levels during the Grenville orogeny. Here, regions of anomalously radiogenic and unradiogenic Pb signatures differentiate the Archean-Proterozoic suture in Ontario from a tectonic duplex in western Quebec.
Keywords: Isotope Geology; Pb Mapping; Grenville Province; Makkovik Province